A Mixed Method Study of Teachers’ Strategies in Reducing Students’ Anxiety levels - Nining Syafitri; Sanaria Maneba; Asti Wahyuni B (Institut Agama Islam Negeri Palopo, 2022)
Abstract This study aims to investigate the level of students' anxiety and determine the teacher's strategies for reducing students' anxiety levels. Foreign Language Classroom Anxiety level Scale (FLCAS) and semi-structured interviews were used to determine the students' anxiety levels and teachers' strategies for reducing the students' anxiety. The result showed that students’ anxiety was at the middle anxiety level, with a mean score of 108.61. Therefore, teachers should employ various strategies, namely establishing a secure environment, speaking English effortlessly, and creating pair and group work. The number of strategies enhances opportunities for students to speak the target language in class and fosters a safe learning atmosphere where students may express themselves freely.